1997
DOI: 10.1111/j.1532-5415.1997.tb03086.x
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Health Care Use and Expenditures Among Frail Older Adults by Payor/Provider Type

Abstract: This study illustrates the complexity of frail older people with respect to their health care expenditures and service use. Expanded efforts to control health care expenditures for frail older people should focus first on those who are dually-enrolled. In addition, because mean medical expenditures for high users enrolled in different payor/ provider groups were surprisingly similar, the data suggest that containing expenditures for individuals in the highest usage group ($20,000+) presents challenges for phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Added to the relatively low occurrence of high cost users, similar to what was found elsewhere [9,16], our study found that expenditure transitions were also characterized by a high proportion of consistently low users and a small proportion of consistently high users, as observed previously by Pearlman et al [17] among frail older adults.…”
Section: Discussionsupporting
confidence: 85%
“…Added to the relatively low occurrence of high cost users, similar to what was found elsewhere [9,16], our study found that expenditure transitions were also characterized by a high proportion of consistently low users and a small proportion of consistently high users, as observed previously by Pearlman et al [17] among frail older adults.…”
Section: Discussionsupporting
confidence: 85%
“…These programs include interventions and incentives to decrease hospital episodes and lengths of stay, efforts to move more health care to the outpatient setting, closer scrutiny of the medical necessity for services, decreasing reimbursement for professional fees, and increased oversight and attention to fraud and abuse 2–7 . The last decade has also seen larger numbers of older adults moving into managed healthcare plans, the growth of increasingly larger healthcare systems, and a renewed interest in the potential for decreasing or delaying costs through improvements in preventive health and lifestyle behaviors 8–15 …”
Section: For Editorial Comment See P 1478mentioning
confidence: 99%
“…Frailty reflects a common view of aging, indicating a critically exhausted functional reserve [54]. The recognition of frailty is particularly useful in planning cancer chemotherapy in older individuals.…”
Section: Frailtymentioning
confidence: 99%
“…The frail older cancer patient needs a different approach to chemotherapy prescription. Sarcopenia, inflammation, and poor nutritional status are associated with frailty in older people [52, 54, 55]. The factors have the potential to significantly affect the clinical pharmacology of cancer chemotherapy agents.…”
Section: Frailtymentioning
confidence: 99%